"I Truly Feel Like I Have Been Hustling on My Own": Minority Graduate Students' Experiences in Communication Sciences and Disorders Programs. - Suswaram, Suma; Perelmutter, Bogi; Keuwo, Romaric; Gillispie, Matthew W. (Perspectives of the ASHA Special Interest Groups, 2022)
Purpose: The field of communication sciences and disorders (CSD) is among the least diverse health and education professions in the United States (Luther, 2017). Recruitment efforts have increased the presence of racial and/or ethnic minority students in CSD over the past decade, yet there has been no comparable increase in the membership of professional organizations, indicating a lack of retention. To understand academic-professional retention, we need to know more about the academic experiences of current students. Method: We performed semistructured qualitative interviews with 10 ethnic and/or racial minority clinical and PhD graduate students in CSD programs, focusing on the barriers and challenges they have faced, and the strategies they have developed to navigate their academic environments. Interviews were analyzed using consensual qualitative research procedures. Results: Almost all participants reported experiences of isolation, positive interactions outside the department, and learning to use self-help strategies. Typical themes also included negative interactions within the department (both in an academic and clinical context), and positive interactions primarily with minority peers. The strategies students reported were more varied than their experiences, and included socially focused strategies--for example, reaching out to minority faculty in other departments--as well as individually focused strategies --for example, keeping in mind the temporary nature of a difficult situation. Conclusion: Based on the results, we discuss new approaches and strategies that might help in improving the retention of minority students in CSD programs.